SELF-EXPANDABLE CHITOSAN STENT – A TECHNOLOGY OF FABRICATION - Kovalenko A.V.; Shinkarev R.V.; Borozdina N.A. (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 11. Estestvennye Nauki, 2016)
The possibility of creating a self-expanding stent, consisting of a combination of the saline and the basic form of chitosan have been discussed. The 2 % chitosan solution in 4 % citric acid have been prepared. The spinning solution have been coated onto an inert substrate in a volume of 0.2-0.25 ml/cm2. Chitosan film (saline form) have been obtained by evaporation of the solvent at room temperature under static conditions. Chitosan film thickness have been measured with a micrometer. Samples of chitosan stents have been formed by winding a chitosan film on the plastic tube. The optimal concentration of NaOH and the dwell time for transfer of chitosan in the form of a saline form to basic form have been defined. The stents photos with a hundredfold magnification and AFM-images of the samples surface have been obtained. The estimate of the stent elongation at break (e) (31-46 %) have been evaluated and have been found that the data on this indicator stents are higher than those obtained from the films form with acetic acid (17 %). These results open up the possibility to create biocompatible biliary stents with their subsequent modification of the active drug substance, which gives hope for improvement of treatment results in patients with obstruction of extrahepatic bile ducts.